If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7.43x + 9 = 55.2049 + 3x Reorder the terms: 9 + 7.43x = 55.2049 + 3x Solving 9 + 7.43x = 55.2049 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + 7.43x + -3x = 55.2049 + 3x + -3x Combine like terms: 7.43x + -3x = 4.43x 9 + 4.43x = 55.2049 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + 4.43x = 55.2049 + 0 9 + 4.43x = 55.2049 Add '-9' to each side of the equation. 9 + -9 + 4.43x = 55.2049 + -9 Combine like terms: 9 + -9 = 0 0 + 4.43x = 55.2049 + -9 4.43x = 55.2049 + -9 Combine like terms: 55.2049 + -9 = 46.2049 4.43x = 46.2049 Divide each side by '4.43'. x = 10.43 Simplifying x = 10.43
| 27=d-18 | | .83x-.16=4 | | x/4=10 | | 3w+2=w+7 | | 25x=-625 | | 2x^4=-250x | | 3(r+2)=-1(2r-4) | | 3*(-4)= | | x^2-5=157 | | x^2+x^2=12 | | (-3)*4= | | 16-8x-12=24+20 | | (-2)*(-8)= | | 9-4x+7x+15= | | 9x+17-7x+17=2 | | -5=-15 | | 7x+10=9x-4 | | (3x^2+5x-1)+(x^2-2x-7)=0 | | 6x-x-2x+8=7x | | 2(6x+2x)=2(x*x+12) | | -9.79(27x-65)=78.24(6x+34) | | 3x(x-5)-3x*3*3=-30 | | 5(x-6)-x=0 | | 2x*x+3x=3 | | 2xx+3x=3 | | -(2x-7)=4 | | ln(30)+ln(x)=24ln(x+1) | | x+4=4x-10 | | 1.5p=-0.3 | | 2.2+p=1 | | 2y+3=5 | | z^2-8iz-16=0 |